Idiopathic restrictive cardiomyopathy in children is caused by mutations in cardiac sarcomere protein genes. Issue 11 (8th May 2008) - Kaski, J P; Syrris, P; Burch, M; Tomé-Esteban, M-T; Fenton, M; Christiansen, M; Andersen, P S; Sebire, N; Ashworth, M; Deanfield, J E; McKenna, W J; Elliott, P M
Abstract : Background: Restrictive cardiomyopathy (RCM) is rare in childhood, but has a grave prognosis. The cause of disease in most cases is unknown. Objective: To determine the prevalence of sarcomere protein gene mutations in children with idiopathic RCM. Methods: Twelve patients (9 female, mean age 5.1 years) with idiopathic RCM referred between 1991 and August 2006 underwent detailed clinical and genetic evaluation. Nine had received cardiac transplants at the time of the study. The entire coding sequences of the genes encoding eight cardiac sarcomere proteins and desmin were screened for mutations. Familial evaluation was performed on first-degree relatives. Results: Four patients (33%) had a family history of cardiomyopathy: RCM (n = 2); dilated cardiomyopathy (n = 1) and left ventricular non-compaction (n = 1). Sarcomere protein gene mutations were identified in four patients (33%): 2 in the cardiac troponin I gene (TNNI3) and 1 each in the troponin T (TNNT2) and α-cardiac actin (ACTC) genes. Two were de novo mutations and 3 were new mutations. All mutations occurred in functionally important and conserved regions of the genes. Conclusions: Sarcomere protein gene mutations are an important cause of idiopathic RCM in childhood. We describe the first mutation in ACTC in familial RCM. The identification of RCM in a child should prompt consideration of sarcomere protein disease as a possible cause and warrants clinical evaluation of the family.